2021
DOI: 10.1371/journal.pone.0255354
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with catastrophic health expenditure among slum and non-slum dwellers undergoing emergency surgery in a metropolitan area of South Western Nigeria

Abstract: Background Out of Pocket (OOP) payment continues to persist as the major mode of payment for healthcare in Nigeria despite the introduction of the National Health Insurance Scheme (NHIS). Although the burden of health expenditure has been examined in some populations, the impact of OOP among slum dwellers in Nigeria when undergoing emergencies, is under-researched. This study sought to examine the prevalence, factors and predictors of catastrophic health expenditure amongst selected slum and non-slum communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…The delivery of the healthcare system is being faced with a lot of inequalities, with CHE serving as a fundamental challenge to it. Evaluating the incidence and intensity of HIV-related CHE will help in providing insight into the UHC and also reflect the economic burden of HIV on patients and their families [17,18]. There was a predominance of female respondents of 59.2% in this study, which is consistent with the outcome obtained from another study in Nigeria with 60% females.…”
Section: Discussionsupporting
confidence: 88%
“…The delivery of the healthcare system is being faced with a lot of inequalities, with CHE serving as a fundamental challenge to it. Evaluating the incidence and intensity of HIV-related CHE will help in providing insight into the UHC and also reflect the economic burden of HIV on patients and their families [17,18]. There was a predominance of female respondents of 59.2% in this study, which is consistent with the outcome obtained from another study in Nigeria with 60% females.…”
Section: Discussionsupporting
confidence: 88%
“…For households that sought surgical or trauma care, CHE incidence was associated with residence, socioeconomic status, health insurance status, and sex, age, marital status, education, and employment status of household head– Table 4 . Other factors include old age, hospitalization, healthcare provider type, specialist care, intensive care unit admission, and emergency surgery [ 31 , 40 , 79 , 81 , 82 , 84 , 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found an increase in healthcare expenditure with each additional condition which is consistent with the findings of a previous study which showed mean out of pocket expenditure for OPD visit increased from INR 262.2 for participants with no NCD to INR 431 amongst those who had multimorbidity. Here, it is worth noting that higher OOPE implies a need to pay directly from pocket for utilizing healthcare facilities which gets hampered by the inability to pay as in the case of urban poor ( 33 ). Multimorbidity requires long term use of multiple drugs, periodic investigations and visits to doctor ( 34 ) which is easy for poorer group, an explanation for easy access to healthcare and hence, better diagnosis and continuity of care among this group than the poorest.…”
Section: Discussionmentioning
confidence: 99%